Perioperative evaluation of CT-based body composition as predictors of postoperative outcome following pancreaticoduodenectomy - Cai, Lina; Wang, Sizhen; Xie, Yehua; Zheng, Hengyu; Zhu, Daojun; Xiao, Yi; Wang, Xinbo; Ye, Xianghong (Frontiers in Nutrition, 2025)
BackgroundAlthough malnutrition is a concern for incremental morbidity in pancreatic surgery, there has been a lack of consensus on nutritional assessment and body composition suitable for prediction of postoperative complications following pancreaticoduodenectomy (PD). Our study was performed to assess whether perioperative CT-based body composition were predictors of morbidity after PD.Methods231 patients who underwent PD between 2020 and 2024 were enrolled to evaluate perioperative body composition. Uni and multivariate logistic regression models were applied to analyze the correlation between major complications, clinically relevant postoperative fistula (CR-POPF) and body composition abnormalities.ResultsFor 231 patients, the incidence of sarcopenia and visceral obesity was 151 (65.4) and 97 (42.0). The incidence of complications, major complications and CR-POPF was 68.0, 33.3 and 10.8%. SMI was the only risk factor for complications [odds ratio (OR), 0.92, 95% confidence interval (CI), 0.85–1.00, p = 0.04]. Neither sarcopenia, visceral obesity nor the other body composition had a significant impact on major complications or CR-POPF, while the patients exhibited wide variation in body composition after the surgical trauma. Soft pancreatic texture was the exclusive independent prognostic factor for CR-POPF (OR, 3.23, 95% CI, 1.17–8.89, p = 0.02).ConclusionPatients with depleted skeletal muscle mass were more likely to develop postoperative complications, while there was no association between perioperative sarcopenia or visceral obesity and major complications or CR-POPF. The study highlights that the highly homogenized and fully managed surgical quality may offset the negative effects of nutritional high-risk factors.